Saberes matemáticos identificados em provas do exame de admissão ao ginásio do Colégio São Paulo (1931-1969) - Santos, Rosemary (2017)
This paper presents the results of a research that aimed to identify mathematical knowledge, used in the statements of the questions, of the exams for admission to the gymnasium, between 1931 and 1969. This examination was intended to select students Who had completed primary education and intended to continue their studies, and when they were approved, they entered the first grade of junior high school, in the Gymnasium of the College of São Paulo. The proofs were examined from the CD-ROM organized by Valente (2001) based on the understanding of Chervel (1990) for the docimological apparatus. From the examination carried out in the tests of the years 1931 to 1969, it was possible to identify that what was called arithmetic or elementary calculation, from the implantation of the entrance exam in the Francisco Campos Reform, can be characterized with a certain approximation with the Programs of the time. It was identified that fraction and measures are the mathematical knowledge that were most used, separated or in combination in situations considered practical. In relation to the formatting of the tests, there were changes in the number of questions, going from three to five, and then to the highest number reaching ten questions. From the 1950s onwards, the tests began to be organized into two parts, one in which problems of practical application were arranged, and in the other, problems of direct application of rules or mathematical principles. Effective change in relation to mathematical knowledge has only been identified since 1968, when problems are adopted as indications of the movement of modern mathematics, through the use of the language of sets in the statements of questions, including those dealing with fraction. This is the announcement of a new format for the teaching of Mathematics, which goes beyond the limit of what was nominated elementary calculus prescribed in the Francisco Campos Reform, the time of the implantation of the entrance examination.